دور اليوتوب في تعزيز المعارف التقنيةلدى طلبة جامعة الاغواط - اكرام طريف; زينب قاسمي; د/ عطالله طريف (جامعة عمار ثليجي بالاغواط, 2025)
ملخص: تهدف هذه الدراسة إلى الكشف عن دور منصة اليوتيوب في تعزيز المعارف التقنية لدى طلبة الماستر بجامعة الأغواط، وذلك من خلال استقراء سلوكيات الاستخدام الرقمي وتفضيلاتهم التعليمية في ظل التحول التكنولوجي الذي يشهده قطاع التعليم العالي. وقد اعتمدت الدراسة على المنهج الوصفي التحليلي، مع توظيف أداة الاستبيان لجمع البيانات من عينة مكونة من (75) طالبًا من قسم علوم الإعلام والاتصال، وتم تحليل المعطيات إحصائيًا باستخدام برنامج SPSS. أظهرت النتائج أن نسبة 66.7% من الطلبة يعتمدون على اليوتيوب كمصدر رئيسي للمعارف التقنية، فيما فضّل 78.0% المحتوى المرئي على النصوص التقليدية. كما بيّنت الدراسة أن 74.7% من الطلبة يلجؤون إلى المنصة عند مواجهتهم صعوبات في المحاضرات، في حين عبّر 81.3% عن أن المحتوى في اليوتيوب أكثر بساطة وسهولة للفهم من المراجع الورقية. وأشارت النتائج إلى تزايد الثقة في الأداء الأكاديمي لدى الطلبة المستخدمين لليوتيوب، إلى جانب وعيهم المتزايد بأهمية المحتوى الموثوق، حيث أكد 70.0% أهمية التحقق من مصدر الفيديو قبل الاعتماد عليه. بالمقابل، كشفت الدراسة عن بعض التخوفات من الاعتماد غير المنهجي على المنصة، وضعف المهارات النقدية لدى فئة من الطلبة. أوصت الدراسة بضرورة دمج المحتوى الرقمي المرئي، لاسيما اليوتيوب، ضمن المنظومة التعليمية الجامعية بطريقة تربوية موجهة، مع العمل على تنمية مهارات التحقق والتفكير النقدي لدى الطلبة، وتعزيز المحتوى العربي المتخصص في المجال التقني. الكلمات المفتاحية: يوتيوب، معارف تقنية، تعلم ذاتي، محتوى رقمي، طلبة جامعة، إعلام واتصال. Abstract: This study aims to reveal the role of the YouTube platform in enhancing technical knowledge among master's students at the University of Laghouat, by examining their digital usage behaviors and educational preferences in light of the technological transformation witnessed in the higher education sector. The study adopted the descriptive analytical method, using a questionnaire tool to collect data from a sample of (75) students from the Department of Media and Communication Sciences. The data was statistically analyzed using the SPSS program. The results showed that 66.7% of the students rely on YouTube as a primary source of technical knowledge, while 78.0% preferred visual content over traditional texts. The study also revealed that 74.7% of students resort to the platform when facing difficulties in lectures, while 81.3% stated that YouTube content is simpler and easier to understand than printed academic references. The findings indicated increased confidence in academic performance among students who use YouTube, alongside growing awareness of the importance of reliable content, as 70.0% emphasized the need to verify the source of videos before relying on them. Conversely, the study identified some concerns about unmethodical dependence on the platform and a lack of critical skills among a segment of students. The study recommended the integration of visual digital content, especially YouTube, within the university educational system in a pedagogically guided manner, while working on developing students' verification and critical thinking skills and promoting specialized Arabic content in the technical field. Keywords: YouTube, technical knowledge, self-learning, digital content, university students, media and communication.
دراسة ميدانية على عينة من طلبة الماستر علوم الاعلام و الاتصال الاغواط